2017
DOI: 10.1111/spol.12314
|View full text |Cite
|
Sign up to set email alerts
|

Labour Market Integration and Equality for Disabled People: A Comparative Analysis of Nordic and Baltic Countries

Abstract: This article considers the employment situation of disabled people, and disability policies, in three Nordic and three Baltic countries (Denmark, Sweden, Norway, Estonia, Latvia and Lithuania). The analysis is framed by a changing paradigm for disability policy‐making, from compensation towards human rights and in a context of multi‐level governance involving the EU and UN as significant policy actors. The analysis draws on policy analysis and European social survey data to compare outcomes for disabled people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Alternatively, limited public services resources might also affect the status of activities. Additionally, our findings support the previous literature: The gap between policy and practice in employment for people with mild IDs still exists (Hvinden 2004;Halvorsen et al 2016;Kuznetsova et al 2017). These results imply a societal need for an increased focus on people with mild IDs, especially for those not receiving public services who have perhaps fallen through the gaps of public systems that provide help with work inclusion.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Alternatively, limited public services resources might also affect the status of activities. Additionally, our findings support the previous literature: The gap between policy and practice in employment for people with mild IDs still exists (Hvinden 2004;Halvorsen et al 2016;Kuznetsova et al 2017). These results imply a societal need for an increased focus on people with mild IDs, especially for those not receiving public services who have perhaps fallen through the gaps of public systems that provide help with work inclusion.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, our findings support the previous literature: The gap between policy and practice in employment for people with mild IDs still exists (Hvinden 2004;Halvorsen et al 2016;Kuznetsova et al 2017). This may be because most people with IDs receive a disability pension without an assessment of functional level, are never in contact with service providers, and no consideration of workability is performed.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Some empirical research studies have revealed that the medical model of understanding disability plays a very important role in Romania, in which the impairment remains a solid rationale that justifies the use of patriarchal attitudes by the non-disabled towards individuals with disabilities [25]. In most cases, the medical model and the social model are exposed as dichotomous structures, but disability should be viewed neither as purely medical nor as purely social: Individuals with disabilities can often experience problems arising from their health condition [26]. On the other hand, resilience resources and soft skills confirmed their effectiveness in reducing perceived disability impact and improving perceived employability in the case of youth with disabilities [27].…”
Section: Literature Reviewmentioning
confidence: 99%